Small rural tourism businesses’ experience of the COVID-19 Tourism Relief Fund: A case of Coffee Bay - Tshepiso Jonathan Setokoe (Interdisciplinary Journal of Rural and Community Studies)
The rapid spread of the coronavirus (COVID-19) has brought economies around the world to a complete halt. Given the restrictive measures implemented by governments to mitigate the damage caused by the virus, many sectors of the economy have been severely affected, with tourism being one of the hardest hit. This article aims to explore and evaluate the experiences of small tourism businesses operating on the outskirts in relation to the Tourism Relief Fund provided by the South African government during the COVID-19 pandemic. Drawing from an interpretive research paradigm, the study adopted a qualitative approach, using semi-structured interviews to gather data. The resulting data was then analysed using NVivo version 12, which generated a comprehensive observation report. The findings indicated that the South African government made concerted efforts to assist tourism businesses in surviving the worst humanitarian crisis of the 21st century. However, the findings also revealed numerous shortcomings that confirmed existing literature, particularly with regard to unconstitutional qualifying criteria. Furthermore, the study found that businesses, especially informal ones that cater to tourists and provide employment, were frustrated by their ineligibility for the Tourism Relief Fund due to qualifying criteria such as registration. In conclusion, the study recommends that the government and policymakers implement more flexible transformation policies, especially during times of crisis.